Molecular beam epitaxy of free-standing bulk wurtzite AlxGa1-xN layers using a highly efficient RF plasma source - Novikov, Sergei V.; Staddon, C.R.; Sahonta, S-L; Oliver, R.A.; Humphreys, C.J.; Foxon, C.T. (Wiley-VCH Verlag Gmbh & Co, 2016)
Recent developments with group III nitrides suggest AlxGa1-xN based LEDs can be new alternative commer-cially viable deep ultra-violet light sources. Due to a sig-nificant difference in the lattice parameters of GaN and AlN, AlxGa1-xN substrates would be preferable to either GaN or AlN for ultraviolet device applications. We have studied the growth of free-standing wurtzite AlxGa1-xN bulk crystals by plasma-assisted molecular beam epitaxy (PA-MBE) using a novel RF plasma source. Thick wurtz-ite AlxGa1-xN films were grown by PA-MBE on 2-inch GaAs (111)B substrates and were removed from the GaAs substrate after growth to provide free standing AlxGa1-xN samples. Growth rates of AlxGa1-xN up to 3 μm/h have been demonstrated. Our novel high efficiency RF plasma source allowed us to achieve free-standing bulk AlxGa1-xN layers in a single day’s growth, which makes our MBE bulk growth technique commercially vi-able.